Peningkatan Kualitas Aparat Pemerintah Desa Sebagai Faktor Penentu Keberhasilan Pembangunan (Suatu Studi Di Kecamatan Rainis Kabupaten Kepulauan Talaud) - Laloma, Alden (JURNAL ADMINISTRASI BISNIS, 2014)
This study departed from the indication of the low success of rural development, especially in sub district Rainis Talaud Islands. This is presumably related to the low quality of village government officials, so that the research aims: (1) to analyze the relationship between the quality of human resources with the village government official development success. (2) to clarify, whether the success of the development will increase if an increase in the quality of human resources village officials. (3) to determine the influence / contribution of human resource quality village government officials to the success of development in the District Rainis. The results of the analysis of the data showed that: (1) That the average quality village government officials, such as: the level of formal education, skills, health / nutrition and rural development success rates in their respective villages, also is in the category